Construindo significados para a linguagem algébrica com o auxílio do jogo codificação-decodificação - Oliveira, Marília Barros de (2004)
The purpose of this paper was to investigate the formation of algebraic language and the construction of its meanings supported by the coding/decoding game. The study set out to answer the question "What are the contributions that the coding/decoding game brings to the construction of meanings of the algebraic language?". I to answer the question, an experimental work was developed with two groups of Sixth Grade Fundamental School students in São Paulo municipal public educational system. The research introduced a learning intervention divided in two fases and three diagnostics instruments pre, intermediate and post tests applied at the beginning, middle and at the end of the learning intervention. One of the groups - the experimental group - participated in the application of the tests, in the coding/decoding game (Phase I of intervention) and in the problem solving activities, establishing connections between the game and formal Algebra (Phase II of intervention). The other group - the control group - participated in the application of diagnostic instruments, in the learning of how to solve equations (Phase I of intervention) and in the learning of how to solve complex equations and problems (Phase II of intervention) The results indicate a superior algebraic performance in the experimental group in relation to the control group. Such superiority was even more evident in the exercises concerning the algebraic language. These data allow the conclusion that the introduction to Algebra supported by the coding/decoding game brings about significant results for the algebraic objects meaning constitution